Mental health during the COVID-19 quarantine in five countries (One Health & Risk Management, 2021)
Introduction. In the current COVID-19 pandemic governments and health entities urgently responded to the biological threat developing diagnostic tests, treatments, vaccines, additionally the economic concerns were approached, however there is little effort directed to the mental health, which is part of the holistic concept of health, and from where interventions for the prevention of contagion and coping with the disease and its consequences can be focused. The present study sought to describe, compare, and analyze the association of the perceived stress, coping strategies, emotional regulation, hopelessness, impact of the event, psychological distress, suicidality, as components of mental health, and sociodemographic characteristics during the quarantine in various countries in Europe and Latin America.Material and methods. Multicentric and epidemiological study approved by the Ethics Committee of the Universidad Cooperativa de Colombia. Convenience online snowball sampling of general population and university students. The questionnaire contained the informed consent, sociodemographic data, and the Impact of Event Scale-Revised, Perceived Stress Scale, Coping Orientations to Problems Experienced, Emotion Regulation Questionnaire, Symptom Check-List-90 Revised, Beck's Hopelessness Scale, and Okasha Suicidality Scale. Data were collected between April and June 2020.Statistical analysis: Internal consistency of scales was estimated by Cronbach's alpha. Normality of distribution was assessed by Kolmogorov-Smirnov tests. Univariate (Kruskal-Wallis test, Spearman correlation) and multivariate analyses (Generalized Linear Models) were performed using STATA 16.Results. 1.179 participants (27.48% male) aged between 15 to 76 years (M=33.52, SD=13.4) from Colombia (N=356), Brazil (N=364), Mexico (N=202), Italy (N=166), and Spain (N=91). The majority are students and workers, whit high level of education, and living with family during the quarantine. There are significant differences in the medians of all variables among countries and sociodemographic characteristics showing greater psychological affectation in young people, students, women, and inhabitants of Brazil, Italy and Spain. Most variables correlate with each other in a statistically significant way as theoretically expected.Conclusions. Due to the complexity of the pandemic, there are differences in terms of contagion containment measures, restrictions, laws and sanctions, government and health authorities’ management, type of information disseminated by media, resources available for diagnoses, treatments and aid, number of infections and deaths, job and economic losses, that significantly affect the impact in mental health worldwide. The results of the present research contribute to the understanding of mental, emotional and behavioral reactions of people across different countries and according to sociodemographic characteristics and underline the urgency of monitoring mental health in vulnerable groups, in order to design specific prevention and intervention programs.